1993
DOI: 10.1016/0954-6111(93)90052-2
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary suppression of cough induced by inhalation of capsaicin in healthy volunteers

Abstract: The aim of the present study was to investigate the voluntary suppression of cough in response to capsaicin inhalation in healthy volunteers, and to determine if the dose-response curve to capsaicin was significantly altered when volunteers were asked to suppress their cough response. The quantification of the degree of voluntary suppression of induced cough could provide a new methodology for screening antitussive agents as antitussives may act by influencing voluntary control of cough. Cough was induced by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 3 publications
3
80
0
1
Order By: Relevance
“…The utility of this stimulus is that, when inhaled, capsaicin evokes both coughing and the associated urge to cough (Davenport et al, 2002;Mazzone et al, 2007). Furthermore, capsaicin-evoked coughing can be consciously suppressed (Hutchings et al, 1993;Mazzone et al, 2007). Our present data extend our previous fMRI analysis of capsaicin-evoked urge to cough (Mazzone et al, 2007(Mazzone et al, , 2009b, confirming activations associated with capsaicin challenge that encompass sensory, motor, and limbic structures, some of which overlap with those activated during cough.…”
Section: Supramedullary Activations After Capsaicin Challengesupporting
confidence: 79%
“…The utility of this stimulus is that, when inhaled, capsaicin evokes both coughing and the associated urge to cough (Davenport et al, 2002;Mazzone et al, 2007). Furthermore, capsaicin-evoked coughing can be consciously suppressed (Hutchings et al, 1993;Mazzone et al, 2007). Our present data extend our previous fMRI analysis of capsaicin-evoked urge to cough (Mazzone et al, 2007(Mazzone et al, , 2009b, confirming activations associated with capsaicin challenge that encompass sensory, motor, and limbic structures, some of which overlap with those activated during cough.…”
Section: Supramedullary Activations After Capsaicin Challengesupporting
confidence: 79%
“…Therefore, it has been proposed that C-fibre activation results in the conscious perception of airway irritation and in respiratory sensations ultimately leading to cough . Accordingly, human subjects can voluntarily suppress capsaicin-induced cough at least up to a certain stimulus intensity (Hutchings et al, 1993). Nevertheless, we are confident that the observed cough responses and differences in cough frequency do not entirely depend upon supramedullary influences, since prior to each trial subjects were carefully instructed to avoid any attempt to facilitate or inhibit cough, that is, they were recommended to cough freely when they could not abstain from doing so.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hutchings, Morris, Eccles, & Jawad (1993) have demonstrated that reflexive coughing to capsaicin can be voluntarily suppressed. This indicates that either cortical inhibition of RC is possible, or alternatively, that a true RC has not been initiated at all.…”
Section: Cough Reflex Testingmentioning
confidence: 99%